Justification of conditions for research on a laboratory biogas plan - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila (My University, 2014)
The residence time of microorganisms in the environment (retention time) is considered to be one of the factors of any microbiological process. To provide effective decomposition of complex organic compounds up to СН4 and СО2 it is necessary that microorganisms were enough sufficient and their presence in the environment was sufficient as well in order to provide metabolism of substrate and thus there was no bacteria leaching. The paper presents the calculation of mixed nutrients for methane generation process as well as the basic parameters affecting the qualitative biogas production process.
Keywords: biogas; methane generated bacteria; fermented mass; green mass; anaerobic process; energy value